Enhancing Critical Thinking Skills of Prospective Elementary School Teachers: A Study on Problem-Based Learning Approach - Dewi Indrapangastuti; Wahyudi Wahyudi; Rokhmaniyah Rokhmaniyah (STAI Hubbulwathan Duri, 2024)
Critical thinking is a higher-order thinking skill that must be fostered during learning. This study aims to provide insights into the achievement of critical thinking skills among students through the implementation of the problem-based learning model in the geometry course. The research methodology employed in this study is descriptive in nature. The participants consisted of 40 Primary School Teacher Education students, who were divided into high, medium, and low-ability groups. Data were collected through written tests and observations. Twelve indicators of critical thinking skills were measured, with ten indicators assessed through written tests and two indicators through observations. The data were analyzed using quantitative descriptive analysis techniques. The study's findings indicate that students' critical thinking skills, as assessed through tests and observations, are considered good in the high, medium, and low groups. This is evident from the average percentages of 83.16% for the high group, 76.40% for the medium group, and 72.08% for the low group, respectively. Students in the high-ability group demonstrated a significantly excellent level of critical thinking skills. In conclusion, applying the PBL model significantly enhances students' critical thinking abilities.